The Role of Morality in Moderating the Effect of Cash Internal Control and Financial Pressure on Fraud Tendency - Sumantri, I G A N Alit; Ni Putu Budiadnyani; Putu Pande R. Aprilyani Dewi; I G A A Pramita Indraswari; Ni Putu Eva Yuni Poniari (Jurnal Ekonomi, 2024)
This study examines how morality affects the influence of cash internal controls and financial pressure on accounting fraud tendencies. Accounting fraud, a dishonest practice in financial reporting or management, can harm an organization's accountability and related parties. Understanding the contributing factors is crucial for effective fraud prevention and detection. This paper investigates how an individual's moral values impact the relationship between cash internal controls, financial pressure, and the propensity for fraudulent actions. By exploring morality's moderating role, the study aims to inform comprehensive strategies to mitigate accounting fraud. Using survey data from financial professionals, regression analysis showed that strong cash internal controls can reduce fraud tendencies, but this effect weakens under high financial pressure. Importantly, individuals with a stronger moral compass are less likely to engage in fraud, even when facing financial pressure. These findings underscore the critical role of personal ethics and integrity in shaping fraud-related decision-making. The implications can guide policymakers, organizational leaders, and the financial community in promoting ethical practices and deterring fraudulent activities.